1994
DOI: 10.1038/ki.1994.190
|View full text |Cite
|
Sign up to set email alerts
|

Opposite renal effects of a PGE1 analog and prostacyclin in humans

Abstract: Renal effects of prostaglandins have been widely investigated in anesthetized animals, but in contrast only few studies have been devoted to healthy and diseased humans. Recently, both prostacyclin and a stable analog of PGE1, misoprostol, have been available for therapeutic purposes in clinical conditions associated with peripheral or renal vasoconstriction; however, the renal effects have not been defined. We have therefore studied the acute renal effects of PGI2 5 ng.kg/min intravenously and of misoprostol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
3
5
1
Order By: Relevance
“…To our knowledge, the impact of infusion of a PGI 2 analogue has not previous been investigated in CsA-treated subjects, but studies in patients with essential hypertension and thrombangiitis obliterans have likewise demonstrated systemic [12,13] and renal vasodilatation [13] by infusion of iloprost in the same dose as the present study, but have contrary to our findings also demonstrated a large increase in GFR [12,13], and a significant increase in the filtration fraction [13]. More comparable with the present results is the study of Natov et al, who investigated the effect of PGI 2infusion in normal volunteers, and demonstrated a decrease in arterial blood pressure, an increase in renal plasma flow, with no change in GFR, and a decrease in filtration fraction [15]. It seems paradoxical that iloprost should abolish CsA-induced vasoconstriction without any impact on the decline in GFR.…”
Section: Discussionsupporting
confidence: 74%
“…To our knowledge, the impact of infusion of a PGI 2 analogue has not previous been investigated in CsA-treated subjects, but studies in patients with essential hypertension and thrombangiitis obliterans have likewise demonstrated systemic [12,13] and renal vasodilatation [13] by infusion of iloprost in the same dose as the present study, but have contrary to our findings also demonstrated a large increase in GFR [12,13], and a significant increase in the filtration fraction [13]. More comparable with the present results is the study of Natov et al, who investigated the effect of PGI 2infusion in normal volunteers, and demonstrated a decrease in arterial blood pressure, an increase in renal plasma flow, with no change in GFR, and a decrease in filtration fraction [15]. It seems paradoxical that iloprost should abolish CsA-induced vasoconstriction without any impact on the decline in GFR.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, when rat blood pressure was measured on day 9, there was a significant rise in diastolic, systolic, and mean pressure in the misoprostol+misoprostol group when compared to vehicle+vehicle group (Table 3). The influence of misoprostol on blood pressure can be explained by the renal vasoconstriction effect of misoprostol [58]. Furthermore, when misoprostol was co-administered with celecoxib, these blood pressure parameters were further elevated.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been suggested by studies in EP 3 gene-disrupted mice that show a prolonged systemic vasodepressor response to PGE 2 administration that is more pronounced in male mice (10). EP 3 receptor activation may also have renal hemodynamic actions because misoprostol, an EP 2 -, EP 3 -, and EP 4receptor agonist, causes a slight vasoconstriction and decreased glomerular filtration rate in humans (109). Additionally, mice that lack the EP 3 receptor have elevated renal blood flows compared with wild-type mice (9).…”
Section: Cox Metabolites: Vasodilator Prostaglandinsmentioning
confidence: 99%